"Caged Women": Migration, Mobility and Access to Health Services in Texas and Arizona. Issue 1 (1st January 2022) - Bissonnette, Andréanne
ABSTRACT : Borderlands are redefined by the hardening of borders, through border walls, increased internal controls, toughened immigration laws, which creates a climate of fear for undocumented migrants. Over the past years, some states and cities in the United States have enacted restrictive policies regarding access to State-provided services, such as healthcare. The impact of these laws needs to be assessed through the gender lens. This paper uses the metaphor of cages to delve on the study of undocumented migrant women's access to healthcare services when the intersection of immigration and healthcare laws creates a restrictive environment, through the case study of Arizona and Texas. It first analyzes the impact on undocumented migrant women's physical health, addressing preventive and emergency care and reproductive and sexual healthcare. Secondly, it addresses the impact of that intersection on women's psychological health, assessing how these policies, when combined, worsen the impacts of past traumas and create new ones while restricting access to psychological services. It demonstrates that undocumented migrant women are affected in specific ways by the intersection of immigration and healthcare laws as it exacerbates the multiple oppressions they experience as low-income women of color without legal status.